Trace elements in reindeer from Rybatsjij Ostrov, north western Russia - Bernhoft, Aksel; Waaler, Thor; Mathiesen, Svein D.; Flåøyen, Arne (Rangifer, 2002)
Reindeer (Rangifer tarandus tarandus) grazing the Rybatsjij Ostrov peninsula, north western Russia, northeast of the industrial towns of Nikel and Zapoljarnij, were analysed for hepatic concentrations of trace elements [arsenic (As), cadmium (Cd), chromium (Cr), cobalt (Co), copper (Cu), lead (Pb), mercury (Hg), nickel (Ni), selenium (Se), and zinc (Zn)] by atomic absorption spectroscopy. The median (range) concentrations (jig/g wet weight) deter¬mined in liver samples from 40 reindeer with even sex ratio and representation from different age classes were As 0.035 (0.017-0.048), Cd 0.34 (0.15-1.2), Cr 0.008 (<0.002-0.022), Co 0.09 (0.06-0.12), Cu 98 (29-220), Pb 0.56 (0.23-1.0), Hg 0.16 (0.08-0.31), Ni 0.027 (<0.020-0.13), Se 0.88 (0.56-1.3) and Zn 37 (24-105). The concentrations of Cd increased and Ni decreased with age. The measured liver concentrations were below levels of toxicological sig¬nificance to the animals. It can be inferred that there is no risk with the measured trace elements to human health associated with the consumption of meat from these reindeer.